Assessment of cytotoxicity and sensitization potential of intradermally injected tattoo inks in reconstructed human skin. (17th June 2021) - Karregat, Joey J. J. P.; Rustemeyer, Thomas; van der Bent, Sebastiaan A. S.; Spiekstra, Sander W.; Thon, Maria; Fernandez Rivas, David; Gibbs, Susan
Abstract: Background: The number of people within the European population having at least one tattoo has increased notably, and with it the number of tattoo‐associated clinical complications. Despite this, safety information and testing regarding tattoo inks remain limited. Objective: To assess cytotoxicity and sensitization potential of 16 tattoo inks after intradermal injection into reconstructed human skin (RHS). Methods: Commercially available tattoo inks were injected intradermally into RHS (reconstructed epidermis on a fibroblast‐populated collagen hydrogel) using a permanent makeup device. RHS biopsies, tissue sections, and culture medium were assessed for cytotoxicity (thiazolyl blue tetrazolium bromide assay [MTT assay]), detrimental histological changes (haematoxylin and eosin staining), and the presence of inflammatory and sensitization cytokines (interleukin [IL]‐1α, IL‐8, IL‐18; enzyme‐linked immunosorbent assay). Results: Varying degrees of reduced metabolic activity and histopathological cytotoxic effects were observed in RHS after ink injection. Five inks showed significantly reduced metabolic activity and enhanced sensitization potential compared with negative controls. Discussion: Using the RHS model system, four tattoo inks were identified as highly cytotoxic and classified as potential sensitizers, suggesting that allergic contact dermatitis could emerge in individuals carrying these inks. These results indicate that an RHS‐based assessment of cytotoxicity and sensitization potential by intradermal tattoo ink injection is a useful analytical tool to determine ink‐induced deleterious effects. Abstract :